Role of different substrates on yield and yield attributing parameters of new strain IGKVm-11 of oyster mushroom (Pleurotus sp.) - Patel, Gopal; Chandrawanshi, S S; Awadhiya, G K (Mushroom Research, 2016)
The effect of five different substrates viz. paddy straw, mung straw, wheat straw, soybean straw and arhar straw on the production of new strain IGKVm-11 of oyster mushroom (Pleurotus sp.) was studied. The number of days required forÂ pawn run was significantly less (14.00 days) on soybean straw followed by mung straw (15.00 days) and the number of fruits and yield wasÂ significantly higher on soybean straw (386.80g/ bag) with 77.36 % biological efficiency and it was closely followed by mung straw (376.00 g/ bag) with 75.2 % biological efficiency. However, these parameters were minimum in wheat straw fallowed by arhar straw, paddy straw but other parameter were maximum.Â